Transnational Korean Television: Cultural Storytelling and Digital Audiences - Ju, Hyejung (Transnational Communication and Critical/Cultural Studies, 2020)
Transnational Korean Television: Cultural Storytelling and Digital Audience provides previously absent analyses of Korean TV dramas' transnational influences, peculiar production features, distribution, and consumption to enrich the contextual understanding of Korean TV's transcultural mobility. Even as academic discussions about the Korean Wave have heated up, Korean television studies from transnational viewpoints often lack in-depth analysis and overlook the recently extended flow of Korean television beyond Asia. This book illustrates the ecology of Korean television along with the Korean Wave for the past two decades in order to showcase Korean TV dramas' international mobility and its constant expansion with the different Western television and their audiences. Korean TV dramas' mobility in crossing borders has been seen in both transnational and transcultural flows, and the book opens up the potential to observe the constant flow of Korean television content in new places, peoples, manners, and platforms around the world. Scholars of media studies, communication, cultural studies, and Asian studies will find this book especially useful.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Sliding Back the Screens: Civil Society and the Erosion of Bureaucratic Control of Television in Japan - Hirano, Chalinee (Television, Regulation and Civil Society in Asia, 2002)
Japan in the 1990s differs vastly from what it had been two or three decades earlier. The Japanese state has undergone such a fundamental change that it has been described as a ‘regime shift’ (Pempel 1998). Although the longterm ruling conservative Liberal Democratic Party (LDP) has returned to power after its defeat in 1993, it no longer has an absolute majority in the Cabinet. Surrounded by numerous scandals and corruption charges, both the government and bureaucracy have undergone major reforms to increase transparency and reduce bureaucratic influence over the policy-making process. The Japanese Diet has, for example, passed the Information Disclosure Law to increase openness in the administration. Economic policies have also been transformed to cope with the malaise characterised by continuing problems of bad loans in the financial sector, rising unemployment and declining manufacturing productivity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Japon (corpus analysé); _Nettoyé

Out of Reach: Television, the Public Sphere and Civil Society in the Philippines - Santos, Josefina M. C. (Television, Regulation and Civil Society in Asia, 2002)
In the uprising of 16-20 January 2001, which ousted former Philippine President Joseph Estrada from power, two forces stood out as pivotal: television (specifically the coverage of the impeachment trial which was the centre of public attention) and civil society (which was instrumental in the uprising itself). In this chapter I argue that notwithstanding the central importance of television in this most recent national political change, the regulation of the sector and its long-term associations with crony capitalism have established barriers to civil society finding its voice on television.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Civic or Civil Contingencies?: Regulating Television and Society in Singapore - Birch, David; Phillips, Marianne (Television, Regulation and Civil Society in Asia, 2002)
Singapore has changed dramatically in the last forty years, moving in the 1960s and 1970s from domestic import substitution to low-cost exportoriented goods. Then in the 1980s developing a regional financial and business hub and now increasingly positioning itself as an exporter of capital and expertise (Courtenay 1995: 90). With exceptionally high economic growth rates most years, a GNP per capita of US$6,000 more than Australia and three times Australia’s annual average growth, Singapore has attracted a high percentage of foreign direct investment. Despite exhibiting similar advantages to Australia in terms of a well-educated workforce, competitive pricing, developed transport and telecommunications and citizens from culturally diverse business, family and personal networks throughout the region, Singapore’s media and resultant civil and civic development has not been as progressive and liberal as Australia’s and indeed has not kept pace. So it would appear that state existence, security and prosperity as desired ends for Singapore do not necessarily rely on an equal strengthening of the public sphere, or at least this is not evident to date.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Singapour (corpus analysé); _Nettoyé

Prime Time Soap Operas on Indian Television - Munshi, Shoma (Routledge India, 2020)
This book examines the phenomenon of prime time soap operas on Indian television. An anthropological insight into social issues and practices of contemporary India through the television, this volume analyzes the production of soaps within India’s cultural fabric. It deconstructs themes and issues surrounding the "everyday" and the "middle class" through the fiction of the "popular". In its second edition, this still remains the only book to examine prime time soap operas on Indian television. Without in any way changing the central arguments of the first edition, it adds an essential introductory chapter tracking the tectonic shifts in the Indian "mediascape" over the past decade – including how the explosion of regional language channels and an era of multiple screens have changed soap viewing forever. Meticulously researched and persuasively argued, the book traces how prime time soaps in India still grab the maximum eyeballs and remain the biggest earners for TV channels. The book will be of interest to students of anthropology and sociology, media and cultural studies, visual culture studies, gender and family studies, and also Asian studies in general. It is also an important resource for media producers, both in content production and television channels, as well as for the general reader.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Koweït (lieu de production du savoir); _Nettoyé

Television Regulation and Media Policy in China - Chin, Yik-Chan (Routledge, 2016)
Since the late 1990s, there has been a crucial and substantial transformation in China’s television system involving institutional, structural and regulatory changes. Unravelling the implications of these changes is vital for understanding the politics of Chinese media policy-making and regulation, and thus a comprehensive study of this history has never been more essential. This book studies the transformation of the policy and regulation of the Chinese television sector within a national political and economic context from 1996 to the present day. Taking a historical and sociological approach, it engages in the theoretical debates over the nature of the transformation of media in the authoritarian Chinese state; the implications of the ruling party’s political legitimacy and China’s central-local conflicts upon television policy-making and market structure; and the nature of the media modernisation process in a developing country. Its case studies include broadcasting systems in Shanghai and Guangdong, which demonstrate that varied polices and development strategies have been adopted by television stations, reflecting different local circumstances and needs. Arguing that rather than being a homogenous entity, China has demonstrated substantial local diversity and complex interactions between local, national and global media, this book will be of interest to students and scholars of Chinese media, politics and policy, and international communications.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Shifts in Korean Television Music Programmes: Democratization, Transnationalization, Digitalization - Jung, Sun (Television Histories in Asia: Issues and Contexts, 2015)
Korea was the fifteenth country in the world to start television broadcasting when it first launched in Seoul in 1956. Since then, the structure, content and policies concerning Korean television have continuously transformed, due largely to changing contextual circumstances such as wide-ranging socio-political democratization and the rise of the neoliberal global economic system and digital technologies. Up until the 1980s, the oligopolistic structure of the two public broadcasting networks  – Korean Broadcasting System (KBS) and Munhwa Broadcasting Corporation (MBC)  – dominated the broadcasting market. However the landscape has dramatically changed since the early 1990s, with 11 newly launched commercial terrestrial broadcasting channels (including Seoul Broadcasting System (SBS) in December 1991) and 153 cable channels when the multichannel television era began (Jin 2005 : 1). A digital satellite television system called Skylife was launched in March 2002, and airs 176 channels at the time of writing. Such changes stem from the shift in the domestic political climate where liberalization and privatization were promoted in assertively practiced neoliberal reform movement in the early 1980s, as well as changes in the global cultural industry environments based largely on globalization and the development of digital technologies. This chapter explores democratization, transnationalization and digitalization, three active factors within Korean television broadcasting by analysing changes and shifts in popular music programmes.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé

Watching Television in Bhutan - Avieson, Bunty (Television Histories in Asia: Issues and Contexts, 2015)
The kingdom of Bhutan drew the international spotlight in 1999 when it became the last nation on earth to introduce broadcast television. It was a deliberate and strategic move by a country that for centuries had chosen to isolate itself from the rest of the world, turning inward to nurture its own culture. The small Himalayan country, whose population in 2013 was estimated at just 733,000, 1 sits uneasily between two feisty behemoths  – China and India – each with over a billion people and an ongoing history of border disputes. Bhutan has long been wary of being swamped, either politically or culturally, by these larger neighbours, as well as the world beyond (Penjore  2004 ).
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Bhoutan (corpus analysé); _Nettoyé

Trust and Television in Globalizing India - McMillin, Divya (Television Histories in Asia: Issues and Contexts, 2015)
Writing a history of Indian television immediately begs the question, how do we want it read? Exhaustive chronological treatments anchor the field (Kumar 2000 ), ideological examinations reveal a Hindu-centric nation with serious consequences for religious and gender minorities (Rajagopal 1996 ; Mitra 1993 ; Van der Veer 1997 ), development analyses demonstrate the failures of a socialist state (F ü risch and Shrikhande 2007 ), and audience studies reveal complex negotiations among multiple identity positions (Mankekar 1999 ). These critical approaches to the study of television in India rightly expose power differentials that facilitate, through the centuries, the inequities of interwoven structures of imperialism, colonialism, casteism, and capitalist patriarchy. Most importantly, they highlight the chronic condition of distrust in postcolonial societies, making it highly challenging to legitimize profi table connections to global circuits as they modernize under the very conditions that once constrained them.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television, Scale and Place-Identity in the PRC: Provincial, National and Global Influences from 1958 to 2013 - Sun, Wanning; Gorfinkel, Lauren (Television Histories in Asia: Issues and Contexts, 2015)
One may argue that Chinese television has already received more than its fair share of attention in the study of Chinese media. As compared with radio and cinema, which developed in the socialist era (1949-78), television has been seen as the dominant medium in the decades of marketization and economic reforms since the late 1970s (Zhu and Berry 2008 ). Television has been studied as a metonym for the ongoing tension and complicity between the Chinese state and the market (e.g., Zhao 1998 ; 2008a) and as a metaphor for the contradictions between a legacy of socialist rhetoric and ethos and a neoliberal market agenda. It is precisely these contradictions that make up what is often referred to as the ‘Chinese characteristics’ (Zhao 2008a; Sun and Zhao 2009 ) of China’s television culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Sange ThakunBangla News Channels and Media-Citizenry - Gupta, Nilanjana (Channeling Cultures: Television Studies from India, 2014)
With special reference to the current scenario in West Bengal, this chapter argues that the rise and popularity of Bangla news channels like Star Ananda, 24 Ghanta, Kolkata TV, and Tara News have resulted in the emergence of a vernacular style of news broadcasting which is quite distinct from that of global or national news media. One major point in this chapter is how the vernacular news channels encourage particular forms of address — the emotional, the intimate and the melodramatic — and how close-ups and sound bites create particular kinds of telegenic political leaders who can use these formal characteristics to their advantage. This chapter explores the ways in which a distinctive kind of vernacular is reconfiguring the nature of political participation itself and hence the notion of citizenship and perhaps even the nature and functioning of the nation-state in India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

From Quinceañera to Miss XV: Coming of Age in Mexican Screen Melodrama - Rios, Sofia (Children, Youth, and International Television, 2022)
This chapter historicises and contextualises the evolution, production, and development of key Mexican screen melodramas over fifty-two years to understand and mediate Mexico’s ambivalence around socioeconomic background, ranother. Perhaps if Televisa had allowed its various ace and religion, gender and worth, family and duty. The chapter demonstrates the importance of localised scholarly inquiry into Mexican audiovisual media that considers not only narrative discourses, content and textual analyses, but also industrial records and practices, marketing campaigns and press releases, archival research and interviews, multimedia synergy, and comparative analysis. For some time, research on Mexican melodrama has had a strong social focus, with several writings about audience engagement, but it is imperative to have more close readings of the texts themselves to understand their cultural context and industrial histories. This research exposes societal changes within Mexico by utilising one of its most omnipresent forms of popular culture and provides a deeper understanding of Mexico’s primary media productions through the use of genre and remake theory. The representations of young women yield a multitude of tensions and ambiguities placed upon Mexican women, which reveal volumes about wider sociocultural expectations.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Globalization and Television: A Study of the Indian Experience, 1990-2010 - Narayan, Sunetra Sen (Oxford University Press, 2013)
This study explores the globalization and liberalization that has occurred in Indian television over the two decades starting from 1990.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Cultural Economy and Television in Jamaica and Ghana: #decolonization2point0 - Hickling Gordon, Deborah (Palgrave Pivot, 2020)
This book proposes contemporary decolonization as an approach to developing cultural economies in the Global South. This book represents the first critical examination and comparison of cultural and creative industries (CCI) and economy concepts in the Caribbean and Africa.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Ghana (corpus analysé); Jamaïque (corpus analysé); Jamaïque (lieu de production du savoir); _Nettoyé

Digital Terrestrial Television Broadcasting (DTTB) in Botswana: Prospects and Challenges - Mosanako, Seamogano; Lesitaokana, William O. (Television in Africa in the digital age, 2021)
The year 2015 was set by the International Telecommunication Union (ITU) for most of its member states globally to switch from analogue to digital terrestrial broadcasting. Digital television broadcasting is generally implied as transmission of broadcast content signals in the form of binary data, speciﬁcally 0 s and 1 s. Digitisation of television merges broadcasting, computing and telecommunications to transform both the way television content is made and consumers interact with content (Chalaby and Segell 1999). Referring to digital content, Flew (2004) suggested that digitisation of media and communication content grows “informatisation” of society.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Botswana (corpus analysé); Botswana (lieu de production du savoir); _Nettoyé

Analysing How Zimbabwe Broadcasting Corporation (ZBC TV) and Eswatini TV (ESTV) Are Adapting to the Digital Era - Lunga, Carolyne M.; Musvipwa, Rosemary (Television in Africa in the Digital Age, 2021)
The internet has impacted on how media organisations do journalism. Many media organisations both print and broadcast now have an online presence to reach out to fragmented audiences that have migrated to online platforms. Television stations have increasingly embraced the use of digital (online) media to gain better access to their audiences in terms of content distribution and audience engagement. The rise of social media platforms such as Facebook, Twitter, YouTube and Instagram have given journalists and media organisations the ability to reach their audiences immediately, with the added beneﬁt of audience responses which come almost immediately. The use of new digital media has created platforms for news stations to share digital clips of news items or excerpts of news programmes to keep the audiences informed or enticed by the highlights.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Eswatini (corpus analysé); Eswatini (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Zimbabwe (corpus analysé); _Nettoyé

Digitization of Television in Kenya: Changing Trends in Content and Consumption - Murunga, Protus; Diang'a, Rachael (Television in Africa in the Digital Age, 2021)
The purpose of this chapter is to examine how the digitization of television has impacted the architecture of television content generation, dissemination consumption in Kenya. Its key motivation is to answer two main questions: How has the digitization shift in Kenya’s television impacted the trends in production, dissemination, reception and consumption of television content; what is the effect of digitization on viewer satisfaction; and how has this shift transformed the role of television medium in the country? The chapter, therefore, answers these questions focusing on the television channels under study, namely, Citizen TV, Kenya Broadcasting Corporation (KBC) and Nation TV (NTV).
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Kenya (corpus analysé); Kenya (lieu de production du savoir); _Nettoyé

Exodus, Access and Inequalities: The Impact of Digital Migration in the Least Developed Countries of Africa - Motsaathebe, Gilbert; Chiumbu, Sarah H. (Television in Africa in the Digital Age, 2021)
There has been a hype regarding the beneﬁts of digital migration, which refers to switchover from analogue to digital broadcasting. Commonly referred to as digital migration, the switchover emanates from a decision made at the International Telecommunications Union (ITU) in 2006 to release a valuable spectrum, which can be used for other services. Other beneﬁts of digital TV include good sound and picture quality and availability of more channels giving viewers more choice. It has also been said that digital broadcasting will save the broadcasting stations’ cost, as transmitting content via digital platforms is less costly than transmitting via the analogue platform (Muthomi 2012). This implies that media houses can capitalise on this migration as a competitive advantage. Countries across the world have been undergoing this necessary switchover from analogue to digital platforms, with varying degree of success. While the merits of digital television are clear, it is not clear how this digitisation will realistically help in bridging habitual inequalities in developing countries.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (lieu de production du savoir); _Nettoyé

Digital Disruption in South African Television News - Stos, Susan (Television in Africa in the Digital Age, 2021)
The term digital “disruption” conjures up negative connotations, with implications of disturbance, interference or interruption. Certainly, virtually every aspect of life has been affected by digitisation, but it has been pointed out that it is detrimental “only for those who chose to ignore it or try to ﬁght it” (“Digital Disruption: What Is It?” 2016, para 2). One case in point is the American company Kodak. Where it once dominated the ﬁlm and camera market for most of the twentieth century, the company recently ﬁled for bankruptcy. Kodak’s mistake was continually opposing the digitisation of the industry and failing to read the writing on the wall (“Digital Disruption: What Is It?” 2016). Digitisation is as much a reality of life in the newsroom as it is in the boardroom.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Understanding Netflix's Foray into Original Productions in South Africa: A "Jet Plane" and "Helicopter" View - Chambwera, Collen (Television in Africa in the Digital Age, 2021)
Until recently, the South African television industry was dominated by the South African Broadcasting Corporation (SABC), etv, and Multichoice. The SABC and etv are free to air while Multichoice provides a satellite subscription service through its DSTV bouquet. This status quo was broken with the emergence of subscription video on demand (SVOD). While Multichoice launched its SVOD service, Showmax, in 2015, greater disruption happened in January 2016 when the current most successful global company in SVOD, Netﬂix, simultaneously launched in 130 countries including South Africa. The coming of Netﬂix to South Africa was reportedly greeted by excitement as viewers embraced choice of access to premium television entertainment. Considering that prior to this development, Multichoice had had a near monopoly in provision of premium television content through its DSTV and Showmax, the reported excitement came as no surprise.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Entertaining Africans: Creative Innovation in the (Internet) Television Space - Dovey, Lindiwe (Television in Africa in the Digital Age, 2021)
Despite great heterogeneity, the vast continent of Africa and the diverse people of its countries and diasporas have often been represented through the most reductive, essentialising, and denigrating paradigms— a process that Nigerian writer Chimamanda Adichie Ngozi has referred to as “the danger of a single story”. One of the most dangerous of these paradigms is the developmentalist one, which shoehorns Africa into a western, capitalist teleological framework that overlooks and denies Africa’s production of and participation in forms of leisure, pleasure and entertainment.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Chinese Television and Soft Power Communication in Australia - Li, Mei (Anthem Press, 2019)
Chinese Television and Soft Power Communication in Australia discusses China’s soft power communication approach and investigates information handling between China and its targeted audiences in the eyes of key influencers – intermediate elites (public diplomacy policy elites in particular) in China and Australia. It explores CGTN (with staff from several professional cultures) and conducts a systemic test of how successful/unsuccessful China’s soft power message projection is in terms of congruence between projected and received frames as a pivotal factor of its power status. The analysis is based on a case study of frames in the messaging on Chinese international TV about China’s Belt and Road Initiative and in the minds of Australian public diplomacy policy elites. The question raised is whether and how Australia is listening.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Océanie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; Australie (corpus analysé); Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Producing Domestic Abuse in Pakistani Television: Between Commerce, Ratings and Social Responsibility - Cheema, Munira (Television for Women, 2016)
Before the liberalisation of television in 2000, Pakistan had one terrestrial channel.The Pakistan Television Corporation (commonly known as PTV) had been the statebroadcaster since 1964 and thus PTV content reflected the policies of differentgovernments. Liberal governments relaxed control over gender on screen – womencould be seen without dupatta – while religiously inclined governments brought intheir own agendas with restrictions on appearance of women, such as the dupattapolicy (see, for example, Ali, 1986; Suleman, 1990; Kothari, 2005; Nasir, 2012).1 In2002, the Independent Media Corporation launched its channel Geo News fromPakistan, followed by other networks, marking the formal launch of the policy ofliberalisation of media on television. Presently, five media groups have control of thePakistani media industry, including electronic and print media. These are Inde-pendent Media Corporation, Pakistan Herald Publications, ARY Group, WaqtGroup and Lakson Group (see for example Proffitt and Rasul, 2013). The broad-casting industry in Pakistan follows an advertiser-driven model that is run through asystem of ratings. At the time of the fieldwork reported here (October-April 2011),Media Logic and Gallup were the two operators that determined the popular tastesof consumers through ratings.2
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Auteur.rice PANDC; 5-Autrice; Pakistan (corpus analysé); _Nettoyé

Defining the Nation?: Lebanese Television and Political Elites (1990–2005) - Nötzold, Katharina (Frank & Timme, 2013)
Katharina Nötzold explores whether and how mass media can contribute to nation-building after civil war. Drawing on the example of Lebanon’s audiovisual media organisations, which are mostly privately owned by politicians, she demonstrates how political elites use television to transmit their visions of post-war society. Lebanon’s nation-building process from 1990 to 2005 was characterized by Syrian dominance over political life. From an extensive content analysis of Lebanese news and interviews with analysts, journalists and managers from all Lebanese TV stations, it emerges that political information on television focused more on divisive experiences than cohesive ones. This has underpinned continued sectarianism in Lebanon, in the media as in society at large, and has impeded nation-building. Biographische Informationen Katharina Nötzold is a political scientist and RCUK Research Fellow at the University of Westminster's Arab Media Centre, and she completed her PhD in Media and Communications at the University of Erfurt, Germany. She lived in Beirut and Amman and worked previously for the Center for International Peace Operations, Berlin. She is editor of Westminster Papers in Communication and Culture and author of articles on Arab media and media representations of migrants and Islam. Reihe Medien und politische Kommunikation – Naher Osten und islamische Welt - Band 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; Allemagne (lieu de production du savoir); Liban (corpus analysé); _Nettoyé

Pretty Liar: Television, Language, and Gender in Wartime Lebanon - Khazaal, Natalie (Syracuse University Press, 2018)
"Pretty Liar" explores the rise of language and gender politics on Lebanese television to tell the untold story of the co-evolution of Lebanese television and its audiences and how the civil war of 1975-1991 affected that co-evolution. The shift in public interest in television has been widely acknowledged and interpreted within an institutional context as a victory of the neo-liberal entrepreneurship of a new, agile brand over the government inefficiency of Lebanon's national station, Télé Liban. Yet, the role of the Lebanese Civil War in reshaping national television and broadcasting in Arab media following the emergence of the Lebanese Broadcasting Company in 1985 has been unexplored. Based on empirical data and grounded in theory by Arab and global researchers, "Pretty Liar" offers textual analyses of five Lebanese fictional series, three major and several additional periodicals, and nine literary works, and provides context from unscripted interviews with television administrators, anchors, actors, and freelance contributors, print journalists, and audience members. Khazaal seeks to offer new insight into how entertainment television became a site for politics and political resistance, feminism, and the cradle for post-war Lebanon due to the shift in practices and standards of legitimacy. The history of television in Lebanon is not merely the history of technology and business, Khazaal argues, but rather the history of a people and their continuing quest for a responsive television even during times of civil unrest.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Liban (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Watching Si Doel: Television, Language and Identity in Contemporary Indonesia - Loven, Klarijn (BRILL, 2008)
While television in today's world increasingly displays a global character, national television systems are still firmly rooted in a specific locality. But in what ways does this locality actually shape the content and performance of national television? What is the significance of local cultures and local languages in these processes of mediation? And how do the local, the national, and the global intersect in discourses of and discourse on television? Taking a critical discourse analysis perspective, Watching Si Doel investigates these and related questions in the context of contemporary Indonesia. Starting from the nationwide popularity of the local television serial Si Doel Anak Sekolahan ("Educated Doel"), it examines the various ways in which the national government, Indonesian television producers, and local audiences shape, interpret, and struggle over the meaning of the phrase 'national television'. In doing so, the book explores what Indonesian television at the turn of the century sounds and looks like--and, significantly, ought to sound and look like--according to those who create and control television and those who watch and interpret it. While providing insight into the production, nature, and reception of television discourse in general, this book particularly seeks to clarify the relationship between television, language, and power in late New Order and post-Soeharto Indonesia.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; Indonésie (corpus analysé); Pays-Bas (lieu de production du savoir); _Nettoyé

Telly-Guillotined: How Television Changed India - Shah, Amrita (SAGE Publications India Pvt, Ltd., 2019)
Fist-fights in television studios, dwindling media autonomy, sensationalism, fake news, religious hate, abusive trolls, political spin ... How did we get here? Three decades ago, before economic liberalization, came the expansion and privatization of Indian television. Technological innovation and easing of government controls offered the prospect of journalistic independence, artistic creativity and an empowered citizenry. This was rendered illusory by runaway growth and untrammelled commercialization. In that thwarted promise of the late 20th century lie the seeds of Indian democracy's current crisis. Telly-Guillotined: How Television Changed India tells the story of how technology was usurped, first by propagandists, then by the market. Going behind the scenes of the world′s greatest media explosion, this book describes the impact of consumerism on the newsroom, the shaping of a new cultural politics and the rise of a new politics of seduction. In a landscape of technological innovation, blurred boundaries and sensory overload, Amrita Shah paints a picture of the Fourth Estate′s challenging future.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Muy buenas noches: Mexico, Television, and the Cold War - Gonzalez de Bustamante, Celeste (Nebraska Paperback, 2013)
By the end of the twentieth century, Mexican multimedia conglomerate Televisa stood as one of the most powerful media companies in the world. Most scholars have concluded that the company’s success was owed in large part to its executives who walked in lockstep with the government and the Partido Revolucionario Institucional (PRI), which ruled for seventy-one years. At the same time, government decisions regulating communications infrastructure aided the development of the television industry. In one of the first books to be published in English on Mexican television, Celeste González de Bustamante argues that despite the cozy relationship between media moguls and the PRI, these connections should not be viewed as static and without friction. Through an examination of early television news programs, this book reveals the tensions that existed between what the PRI and government officials wanted to be reported and what was actually reported and how. Further, despite the increasing influence of television on society, viewers did not always accept or agree with what they saw on the air. Television news programming played an integral role in creating a sense of lo mexicano (that which is Mexican) at a time of tremendous political, social, and cultural change. At its core the book grapples with questions about the limits of cultural hegemony at the height of the PRI and the cold war.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Inuit Visual and Sensate Sovereignty in Alethea Arnaquq-Baril’s Angry Inuk - Burelle, Julie (Canadian Journal of Film Studies, 2020)
L’auteure soutient que le documentaire de 2016 d’Alethea Arnaquq-Baril, Angry Inuk (Inuk en colère), crée, grâce au cinéma, des espaces de « souveraineté visuelle » centrés sur l’« agentivité sensorielle » inuite (Raheja, 2010 ; Robinson, 2016). La réalisatrice propose un recadrage, selon un point de vue inuit, de la rhétorique dominante entourant la chasse aux phoques, pratique décriée violemment par des groupes de défense des droits des animaux. Plus qu’une simple réfutation de ces discours sudistes, ce film met de l’avant les connaissances inuites en lien avec le territoire et la gestion des ressources et remet en question les argumentaires libératoires soutenus par ces organismes, dont les raisonnements reconduisent des dynamiques coloniales plutôt que de les ébranler. Comme l’évoque son titre, le documentaire riposte à l’ire des protestataires anti-chasse aux phoques (dont la voix s’impose souvent au détriment des voix inuites, généralement tues), en créant un espace d’expression pour la colère inuite, présentée à la fois comme carburant et comme point de départ légitime et valide de la lutte contre les organismes en question. De façon centrale, le film met en scène des récits de chasse aux phoques s’appuyant sur une « agentivité sensorielle » inuite qui, aux yeux de Dylan Robinson, se manifeste sous la forme de « modes d’expression qui, à la fois, affirment une force culturelle et exercent une puissance affective auprès des personnes présentes ». Arnaquq-Baril propose ainsi des représentations de rires partagés, d’un froid ressenti, de sons joyeux de consommation communautaire de diverses parties du phoque, de même que des photos tirées de la campagne Twitter menée autour du mot-clic #sealfie ; cette campagne médiatique, ancrée dans une célébration humoristique et fière de la chasse inuite aux phoques, se veut en ce sens un contre-point au discours affectif simpliste et méprisant des organismes anti-chasse. En s’articulant autour de la résilience complexe propre aux Inuits, Inuk en colère incarne en soi une forme de souveraineté inuite, s’imposant au sein des récits qui participent à la sensibilisation du public quant aux enjeux entourant cette chasse. En outre, le film invite l’auditoire à réfléchir aux avenirs autochtones et à envisager de quelles manières l’activisme pour la défense des droits des animaux peut être décolonisé afin qu’il ne mène pas à la reconduction de dynamiques violentes d’extractivisme et de colonisation.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Aboriginal Territories in Cyberspace - Lewis, Jason E.; Fragnito, Skawennati T. (Cultural Survival Quarterly., 2005)
Indigenous peoples are making their own spaces online, using art as the backdrop for cross-cultural dialogue. Cyberspace—the websites, chat rooms, bulletin boards, virtual environments, and games that make up the internet—offers Aboriginal communities an unprecedented opportunity to assert control over how we represent ourselves to each other and to non-Aboriginals. This article introduces the concept of Aboriginally determined territories in cyberspace and discusses how these can be defined, maintained, and expanded. We will do this within the Canadian context, though much of the discussion is pertinent to Aboriginal communities in other parts of the world. We draw on lessons learned from creating and curating CyberPowWow, an Aboriginally determined online gallery, to propose Aboriginal Territories in Cyberspace, a series of initiatives to expand Aboriginal presence online. These include expanding CyberPowWow into an ongoing community of new media artists addressing Aboriginal issues; developing Skins, a project in which elders work with youth to explore tribal stories through the use of online virtual environments; and laying the foundations for Within Reservations, which will function as a blueprint for equipping Aboriginals for full participation in the ongoing revolution in networked information technologies.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Afterlives of Indigenous archives: essays in honor of The Occom Circle - Schweitzer, Ivy; Henry, Gordon (Dartmouth College Press, 2019)
"Afterlives of Indigenous Archives offers a compelling critique of Western archives and their use in the development of “digital humanities.” The essays collected here present the work of an international and interdisciplinary group of indigenous scholars; researchers in the field of indigenous studies and early American studies; and librarians, curators, activists, and storytellers. The contributors examine various digital projects and outline their relevance to the lives and interests of tribal people and communities, along with the transformative power that access to online materials affords. The authors aim to empower native people to re-envision the Western archive as a site of community-based practices for cultural preservation, one that can offer indigenous perspectives and new technological applications for the imaginative reconstruction of the tribal past, the repatriation of the tribal memories, and a powerful vision for an indigenous future."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

You Want to Do What with Doda’s Stories? Building a Community for the Skins Workshops on Aboriginal Storytelling in Digital Media - Lewis, Jason E.; Fragnito, Skawennati (Community-Based Multiliteracies & Digital Media Projects : Questioning Assumptions and Exploring Realities, 2014)
Aboriginal Territories in Cyberspace (AbTeC) is a research network of artists, academics and technologists centrally concerned with Indigenous representation in, and production of, digital media (AbTeC, 2008). AbTeC investigates and identifies ways for Indigenous peoples to tell our stories via networked technologies, and in so doing, strengthen our communities while proactively participating in shaping cyberspace. We are based at Concordia University, in Montreal, Quebec.
Keywords: 1-Histoire de l'art; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Repenser le temps et l'espace, du wampum au selfie - Vigneault, Louise (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
This article considers the way certain Indigenous artists are reviving conceptions of territory and history that are anchored in secular epistemologies and the construction of knowledge. Such conceptions provide a way for these artists to respond to colonial appropriation, reactivate interrupted dialogues, engender new forms of territorialization, and create places of commemoration and memory preservation. Similar to the historiographical deconstruction performed by thinkers and activists such as Vine Deloria Jr. and Taiaiake Alfred, these artists’ works offer a model of autonomy and environmental balance. While some are reviving mnemonic practices, such as the making of wampum, which traditionally preserve memories of alliances and conflicts, others have embraced Internet and selfie technologies as a means of creating new spaces for speech and recognition
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

CyberPowWow: discours chronopolitiques autour des arts et muséographies numériques autochtones - L'Heureux, Isabelle (Université de Montréal, 2018)
Le collectif d'artistes Nation to Nation crée en 1996 CyberPowWow, une galerie d'art numérique autochtone en ligne. Entre 1997 et 2004, le projet voit quatre éditions se succéder et plus d'une vingtaine d'artistes y participer. CPW développe un modèle alternatif pour une production, une diffusion et une critique autodéterminée des arts numériques autochtones au Canada, ce qui lui confère une place importante dans la structuration de cette scène. Le présent mémoire vise à étudier la position de CPW - sa plateforme muséographique et ses œuvres - au sein d'un ensemble de discours chronopolitiques qui opèrent à l'intersection des arts, des technologies numériques et des identités autochtones
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Technologies of Self-Fashioning : Virtual Ethnicities in New Media Art - Jim, Alice Ming Wai (2015)
This paper proposes a theoretical framework with which to dis- cuss the critical engagement of media art projects in Second Life with racialized self-representation, fashion and ethnic dress. Ex- amining Montreal-based Mohawk artist Skawennati’s machinima series, TimeTravellerTM (2008-13), a project of self- determination, survivance and Indigenous futurity, it argues the critically-aware act of ‘virtually self-fashioning’ racialized born- digital identities, or virtual ethnicities, disrupts ways in which today’s vast proliferation of self-technologies enabling the crea- tion, recreation and management of multiple selves, would other- wise remain complicit with neoliberal colour-blind racism
Keywords: 1-Histoire de l'art; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Postcolonial Playgrounds: Games and postcolonial culture - Lammes, Sybille (Eludamos. Journal for Computer Game Culture, 2010)
Many games touch upon issues that are related to the postcolonial culture we live in. Be it in the shape of referring to how it has generated ethnic differences, subscribing to (post) capitalist values of winning and gaining, or by employing militarist strategies that have been partly shaped our colonial histories, cultural notions that are related to our colonial past are often resonant in games. However, one particular strand of strategy games takes the notions of colonialism as its most central focus. Games like Age Of Empires (AOE), Civilization and Rise of Nations, may differ greatly in certain ludological aspects, but all share a strong fascination with colonial history. Through employing colonial techniques of domination like exploring, trading, map-making and military manoeuvring, players create their personal colonial pasts and futures. Even though it is evident that such games share an explicit fascination with colonial history, it remains less clear in what way they may be called postcolonial. In this article I will shed light on why and how such games can be called postcolonial and should even be conceived as one of the most significant arenas to express the tensions and frictions that are part of the postcolonial culture we live in. As postcolonial playgrounds they offer the perfect means to play with and make sense of how colonial spatial practices have shaped contemporary culture. I will argue that the very character of digital games as well as the specific game mechanisms of historical strategy games makes them postcolonial playgrounds par excellence.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Gender and Race in the Gaming World - Nakamura, Lisa (Society and the Internet : how networks of information and communication are changing our lives, 2019)
Age is not alone in shaping real and imagined differences in Internet use. Racial and gender-based stereotypes abound and need to be empirically challenged. This chapter explores the relationships between race, gender, sexuality, and digital cultures in one increasingly significant digital domain—gaming. With a review of previous scholarship on race, gender, and gaming, the author shows that we see few signs of a “post-racial” society being brought into being. In fact, gaming is a digital activity where racism and sexism are commonplace. The chapter thus leaves us with questions about why, when the Internet is a potentially powerful leveling tool in the quest for democracy and fairness, does it continue to be defined by egregious sexism and racism?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

The International Encyclopedia of Media Studies: Media History and the Foundations of Media Studies - Valdivia, Angharad N.; Nerone, John C.; Mayer, Vicki; Mazzarella, Sharon R.; Parameswaran, Radhika E.; Scharrer, Erica; Darling-Wolf, Fabienne; Gates, Kelly (Wiley-Blackwell, 2013)
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Race and Media: Critical Approaches - Lopez, Lori Kido (New York University Press, 2020)
1. Racism and Mainstream Media / Lori Kido Lopez -- 2. Image Analysis and Televisual Latinos / Mary Beltrán -- 3. Visualizing Mixed Race and Genetics / Meshell Sturgis and Ralina L. Joseph -- 4. Listening to Racial Injustice / Dolores Inés Casillas and Jennifer Lynn Stoever -- 5. Branding Athlete Activism / Jason Kido Lopez -- 6. The Burden of Representation in Asian American Television / Peter X. Feng -- 7. Indigenous Video Games / Jacqueline Land -- 8. Applying Latina/o Critical Communication Theory to Anti-Blackness / Mari Castañeda -- 9. Asian American Independent Media / Jun Okada -- 10. Remediating Trans Visuality / Amy Villarejo -- 11. Intersectional Distribution / Aymar Jean Christian -- 12. Podcasting Blackness / Sarah Florini -- 13. Black Twitter as Semi-Enclave / Raven Maragh-Lloyd -- 14. Arab Americans and Participatory Culture / Sulafa Zidani -- 15. Diaspora and Digital Media / Lia Wolock -- 16. Disrupting News Media / Meredith D. Clark -- 17. Latinx Audiences as Mosaic / Jillian M. Báez -- 18. Media Activism in the Red Power Movement / Miranda J. Brady -- 19. Black Gamers' Resistance / Kishonna L. Gray -- 20. Cosmopolitan Fan Activism / Susan Noh.
Keywords: 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Gender, Race, and Class in Media a Critical Reader - Dines, Gail.; Humez, Jean M. (SAGE Publications, 2015)
Incisive analyses of mass media - including such forms as talk shows, MTV, the Internet, soap operas, television sitcoms, dramatic series, pornography, and advertising-enable this provocative third edition of Gender, Race and Class in Media to engage students in critical mass media scholarship. Issues of power related to gender, race, and class are integrated into a wide range of articles examining the economic and cultural implications of mass media as institutions, including the political economy of media production, textual analysis, and media consumption. Throughout, Gender, Race and Class in Media examines the mass media as economic and cultural institutions that shape our social identities, especially in regard to gender, race, and class.
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Learning Race and Ethnicity: Youth and Digital Media - Everett, Anna (The John D. and Catherine T. MacArthur foundation series on digital media and learning, 2008)
An exploration of how issues of race and ethnicity play out in a digital media landscape that includes MySpace, post-9/11 politics, MMOGs, Internet music distribution, and the digital divide.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Racial Logics, Franchising, and Video Game Genres: The Lord of the Rings - Young, Helen (Games and Culture, 2016)
This article explores the ways game adaptations engage with existing popular culture constructions of race within the framework of commercial franchises. Its focus is on games which are part of the so-called “Frodo Franchise” based on Peter Jackson’s Lord of the Rings and The Hobbit films. It considers the role played by licensing agreements, the conventions, and ludic elements of different game genres, the need for new characters and narratives to keep audiences engaged with an existing world, and the opportunity games offer for interactive exploration of a digital world, to illuminate both the challenges to and the opportunities for disrupting conventional representations of race and difference.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé

Computational Blackness: The Procedural Logics of Race, Game, and Cinema, or How Spike Lee's Livin' Da Dream Productively "Broke" a Popular Video Game - Russworm, TreaAndrea M. (Black Camera, 2018)
How have video games evolved to now create meaningful stories about race and sports? This essay examines how Spike Lee's film-within-a-game, Livin' Da Dream (2015), reproduces some existing procedural and racial logics that reflect the desire to constantly manage and contain the centrality of black athletic greatness in mainstream sports and video game culture. While Lee's long-form cinematic model for turning sports video games into narrative games has been emulated across the medium as a whole, fans and gamers continually discuss the film as an evidently "broken" part of the popular NBA 2K video game series. As I argue here, however, the film-within-a-game productively insists on a default blackness when it functions as what I call "procedural cinema" (a rules and process based narrative). Ultimately, in functioning procedurally, Lee's otherwise conservative melodramatic story serves as a particularly instructive example of how computational blackness may, in systematically subverting the rules of the game, signify disruptively both within and against the machine.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À nettoyer; _À vérifier-Cinéma

Feminism in Play - Gray, Kishonna L.; Voorhees, Gerald; Vossen, Emma (Palgrave games in context, 2018)
Feminism in Play focuses on women as they are depicted in video games, as participants in games culture, and as contributors to the games industry. This volume showcases women's resistance to the norms of games culture, as well as women's play and creative practices both in and around the games industry. Contributors analyze the interconnections between games and the broader societal and structural issues impeding the successful inclusion of women in games and games culture. In offering this framework, this volume provides a platform to the silenced and marginalized, offering counter-narratives to the post-racial and post-gendered fantasies that so often obscure the violent context of production and consumption of games culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Japanese Culture Through Videogames - Hutchinson, Rachael (Contemporary japan series ; 80, 2019)
"Examining a wide range of Japanese videogames, including arcade fighting games, PC-based strategy games and console JRPGs, this book assesses their cultural significance and shows how gameplay and context can be analyzed together to understand videogames as a dynamic mode of artistic expression. Well-known titles such as Final Fantasy, Metal Gear Solid, Street Fighter and Katamari Damacy are evaluated in detail, showing how ideology and critique are conveyed through game narrative and character design as well as user interface, cabinet art, and peripherals. This book also considers how Japan' has been packaged for domestic and overseas consumers, and how Japanese designers have used the medium to express ideas about home and nation, nuclear energy, war and historical memory, social breakdown and bioethics. Placing each title in its historical context, Hutchinson ultimately shows that videogames are a relatively recent but significant site where cultural identity is played out in modern Japan. Comparing Japanese videogames with their American counterparts, as well as other media forms, such as film, manga and anime, Japanese Culture Through Videogames will be useful to students and scholars of Japanese culture and society, as well as Game Studies, Media Studies and Japanese Studies more generally."-- Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

History First-Hand: Memory, the Player and the Video Game Narrative in the Assassin's Creed Games - Menon, Lakshmi (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2015)
This paper will look at the convergence of the interactive free flow of video games and the questioning and revisioning of historical continuity using the example of the Assassin's Creed series by Ubisoft. With a story that exists simultaneously in the modern day and the 15th century, the games allow the player to take control of characters and alter, or make possible, events recognisable as historical fact. It plays with both history and memory and history as memory, as the life of the primary player character is being relived through the genetic memories of one of his descendants. Being highly narrative-bound, the Assassin's Creed games use, via the medium of the screen, the rift between history and memory as a central element of narrative, theme, and game design, which this paper will explore. Furthermore, using theories of convergence this paper will examine how video games provide a new, interactive mode of storytelling that is rapidly becoming representative of our age.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

War Games: Memory, Militarism and the Subject of Play - Hammond, Philip; Pötzsch, Holger (Bloomsbury Publishing USA, 2019)
Many of today's most commercially successful videogames, from Call of Duty to Company of Heroes, are war-themed titles that play out in what are framed as authentic real-world settings inspired by recent news headlines or drawn from history. While such games are marketed as authentic representations of war, they often provide a selective form of realism that eschews problematic, yet salient aspects of war. In addition, changes in the way Western states wage and frame actual wars makes contemporary conflicts increasingly resemble videogames when perceived from the vantage point of Western audiences.This interdisciplinary volume brings together scholars from games studies, media and cultural studies, politics and international relations, and related fields to examine the complex relationships between military-themed videogames and real-world conflict, and to consider how videogames might deal with history, memory, and conflict in alternative ways. It asks: What is the role of videogames in the formation and negotiation of cultural memory of past wars? How do game narratives and designs position the gaming subject in relation to history, war and militarism? And how far do critical, anti-war/peace games offer an alternative or challenge to mainstream commercial titles?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

The Work of Postcolonial Game Studies in the Play of Culture - Murray, Soraya (Open Library of Humanities, 2018)
This article considers larger methodological questions of what political work is undertaken when scholars engage in postcolonial critiques of video games within academic intellectual frameworks. What is postcolonial game studies, and what is its purpose, within the context of larger issues of inclusion, representation, diversity, and the challenging of hegemonic power structures? After surveying some of the key literature in postcolonial game studies, the author provides critical frameworks for understanding the means by which these approaches have largely been excluded from video game studies, and their crucial function in operating against the grain of profit and innovation-driven discourses in games. This work is the extension of a larger discussion of inclusion, diversity, and tolerance discourse within the liberal academy, and particularly the functions of postcolonial, postmodern and other critical cultural scholarly interventions. In this article, the author argues for a postcolonial approach to game studies, but one that refuses to be reduced to an institutional cultural labor of due diligence, or according to Slavoj Žižek’s term, a ‘culturalization of politics’. Through the work of Stuart Hall and Sara Ahmed on intellectual diversity work within the context of large systems and academic institutions, this article asserts that the perception that critical theorizations (like postcolonial game studies) exert pressure on efficiency and innovation is greatly outweighed by the rich toolkits they bring to video games as maturing cultural forms.
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Casual Empire: Video Games as Neocolonial Praxis - Harrer, Sabine (Open Library of Humanities, 2018)
As a media form entwined in the U.S. military-industrial complex, video games continue to celebrate imperialist imagery and Western-centric narratives of the great white explorer (Breger, 2008; Dyer-Witheford & de Peuter, 2009; Geyser & Tshalabala, 2011; Mukherjee, 2016). While much ink has been spilt on the detrimental effects of colonial imagery on those it objectifies and dehumanises, the question is why these games still get made, and what mechanisms are at work in the enjoyment of empire-themed play experiences. To explore this question, this article develops the concept of ‘casual empire’, suggesting that the wish to play games as a casual pastime expedites the incidental circulation of imperialist ideology. Three examples – Resident Evil V (2009), The Conquest: Colonization (2015) and Playing History: Slave Trade (2013) – are used to demonstrate the production and consumption of casual empire across multiple platforms, genres and player bases. Following a brief contextualisation of postcolonial (game) studies, this article addresses casual design, by which I understand game designers’ casual reproduction of inferential racism (Hall, 1995) for the sake of entertainment. I then look at casual play, and players’ attitudes to games as rational commodities continuing a history of commodity racism (McClintock, 1995). Finally, the article investigates the casual involvement of formalist game studies in the construction of imperial values. These three dimensions of the casual – design, play and academia – make up the three pillars of the casual empire that must be challenged to undermine video games’ neocolonialist praxis.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Methods for Studying Video Games and Religion - Šisler, Vít; Radde-Antweiler, Kerstin; Zeiler, Xenia (Routledge Studies in Religion and Digital Culture, 2017)
Game studies has been an understudied area within the emerging field of digital media and religion. Video games can reflect, reject, or reconfigure traditionally held religious ideas and often serve as sources for the production of religious practices and ideas. This collection of essays presents a broad range of influential methodological approaches that illuminate how and why video games shape the construction of religious beliefs and practices, and also situates such research within the wider discourse on how digital media intersect with the religious worlds of the 21st century. Each chapter discusses a particular method and its theoretical background, summarizes existing research, and provides a practical case study that demonstrates how the method specifically contributes to the wider study of video games and religion. Featuring contributions from leading and emerging scholars of religion and digital gaming, this book will be an invaluable resource for scholars in the areas of digital culture, new media, religious studies, and game studies across a wide range of disciplines.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Contemporary Sino-Japanese Relations on Screen: A History, 1989-2005 - Kirsch, Griseldis (Bloomsbury Publishing, 2015)
Japan and China look back on a history of friendship as well as friction, particularly in recent decades. As the People's Republic of China's economy began to grow in the 1990s, so did its political weight within Asia and its economical relevance for Japan. Covering the years from 1989 to 2005, this book looks at Sino-Japanese relations through film and television drama in the crucial time of China's ascent to an economic superpower in opposition to Japan's own ailing economy. It provides an overview of how Japan views China through its visual media, offers explanations as to how oppositions between the two countries came to exist, and how and why certain myths about China have been conveyed.Griseldis Kirsch argues that the influence of visual media within society cannot be underestimated, nor should their value be lessened by them being perceived as part of 'popular culture'. Drawing on examples from a crucial 16 years in the history of post-war Japan and China, she explores to what extent these media were influenced by the political discourse of their time. In doing so, she adds another layer to the on-going debate on Sino-Japanese relations, bringing together disciplines such as media studies, history and area studies and thus filling a gap in existing research.
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Gaming at the Edge: Sexuality and Gender at the Margins of Gamer Culture - Shaw, Adrienne (University of Minnesota Press, 2015)
Video games have long been seen as the exclusive territory of young, heterosexual white males. In a media landscape dominated by such gamers, players who do not fit this mold, including women, people of color, and LGBT people, are often brutalized in forums and in public channels in online play. Discussion of representation of such groups in games has frequently been limited and cursory. In contrast, Gaming at the Edge builds on feminist, queer, and postcolonial theories of identity and draws on qualitative audience research methods to make sense of how representation comes to matter. In Gaming at the Edge, Adrienne Shaw argues that video game players experience race, gender, and sexuality concurrently. She asks: How do players identify with characters? How do they separate identification and interactivity? What is the role of fantasy in representation? What is the importance of understanding market logic? In addressing these questions Shaw reveals how representation comes to matter to participants and offers a perceptive consideration of the high stakes in politics of representation debates. Putting forth a framework for talking about representation, difference, and diversity in an era in which user-generated content, individualized media consumption, and the blurring of producer/consumer roles has lessened the utility of traditional models of media representation analysis, Shaw finds new insight on the edge of media consumption with the invisible, marginalized gamers who are surprising in both their numbers and their influence in mainstream gamer culture.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Race-based fantasy realm: Essentialism in the world of warcraft - Monson, Melissa J. (Games and Culture, 2012)
This article explores issues of racial essentialism and ethnicity in the massively multiplayer online role-playing game World of Warcraft (WoW). The fantasy world of Azeroth mirrors elements of real-world race-based societies where culture is thought to be immutably linked to race. The notion of biological essentialism is reinforced throughout the gamescape. Race plays a primary role in the social and political organization of Azeroth. Among other things, race determines alliances, language, intellect, temperament, occupation, strength, and technological aptitude. The cultural representation of the respective racial groups in WoW draws upon stereotypical imagery from real-world ethnic groups (e.g., American Indian, Irish/Scottish, Asian, African, etc.).
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Gaming Cultures and Place in Asia-Pacific - Hjorth, Larissa; Chan, Dean (Routledge studies in new media and cyberculture, 2009)
This collection explores the relationship between digital gaming and its cultural context by focusing on the burgeoning Asia-Pacific region. Encompassing key locations for global gaming production and consumption such as Japan, China, and South Korea, as well as increasingly significant sites including Australia and Singapore, the region provides divergent examples of the role of gaming as a socio-cultural phenomenon. Drawing from micro ethnographic studies of specific games and gaming locales to macro political economy analyses of techno-nationalisms and trans-cultural flows, this collection provides an interdisciplinary model for thinking through the politics of gaming production, representation, and consumption in the region.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Gameplay in the “Zone of Becoming”: Locating Action in the Computer Game - Mukherjee, Souvik (Conference Proceedings of The Philosophy of Computer Games 2008, 2009)
Extending Alexander Galloway’s analysis of the action-image in videogames, this essay explores the concept in relation to its source: the analysis of cinema by the French philosopher Gilles Deleuze. The applicability of the concept to videogames will, therefore, be considered through a comparison between the First Person Shooter S.T.A.L.K.E.R. and Andrey Tarkovsky’s film Stalker. This analysis will compellingly explore the nature of videogame-action, its relation to player-perceptions and its loca-tion within the machinic and ludic schema.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A telenovela brasileira: do nacionalismo à exportação - Santos, Lidia (Caravelle. Cahiers du monde hispanique et luso-brésilien, 2000)
Rentable produit d'exportation diffusé dans 128 pays, le feuilleton télévisé brésilien fait partie du quotidien de la population depuis une trentaine d'années. Si une grande part de son succès repose sur l'exploitation de « la culture des sentiments », dans sa version la plus moderne, il sait aussi plonger au cœur de la réalité comme l'a démontré entre autres avec brio « Le roi du troupeau » (1986) qui mettait en scène le conflit entre les sans-terre et les grands propriétaires terriens.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Género y postcolonialismo en la creación videográfica: mujeres que escriben con la cámara y seducen en la pantalla - López, Xesqui Castañer (Dossiers feministes, 2014)
Postcolonialismo y feminismo utilizan conceptos comunes para el análisis y de/construcción de las narrativas dominantes. En países donde la colonización ha hecho estragos, las mujeres ponen en valor su empoderamiento como protagonistas de su destino. En esta línea las mujeres han aportado sus propuestas feministas para una nueva visión de lo colonial/postcolonial. Este trabajo pretende hacer un chequeo por aquellos trabajos videográficos de mujeres que, después de haber sido colonizadas, han realizado una descolonización cultural, situando su creatividad en varios continentes.
Keywords: 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _À vérifier-Cinéma

Indigenous Art: New Media and the Digital - Igloliorte, Heather; Nagam, Julie; Taunton, Carla (Public : art, culture, ideas, 0845-4450 ; volume 27, issue 54, 2016)
Indigenous Art New Media and the Digital convenes leading scholars, curators, and artists from the Indigenous territories in Canada, the United States of America, Australia, and Aotearoa (New Zealand). It brings forth urgent conversations about resistance to colonial modernism, and highlights the historic and ongoing use of technology by Indigenous communities and artists as vehicles of resilience and cultural continuity. This issue ignites productive dialogue around the definitions of new and digital media art and practice-based work within the framework of Indigenous art and theory
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Call it a Vision Quest : Machinima in a First Nations context - Lapensée, Elizabeth; Lewis, Jason E. (Understanding Machinima Essays on Filmmaking in Virtual Worlds, 2013)
Article sur les machinimas de l'artiste Skawennati (Kanien'kehá:ka) et du travail du laboratoire d'ABTEC (Aboriginal Territories on cyberspace) à l'Université Concordia.
Keywords: 1-Histoire de l'art; 2-Recherche-création; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À vérifier-Jeu vidéo

Transference, Tradition, Technology: Native New Media Exploring Visual & Digital Culture - Townsend, Melanie A.; Hopkins, Candice (Walter Phillips Gallery Editions, 2005)
Transference, Tradition, Technology explores Canadian Aboriginal new media and references the work of artists within a political, cultural and aesthetic milieu. The book constructs a Native art history relating to these disciplines, one that is grounded in the philosophical and cosmological foundations of Aboriginal concepts of community and identity within the rigour of contemporary arts discourse. Approachable in nature but scholarly in content, this book is the first of its kind. A text book for students and teachers of Canadian Aboriginal history and visual and media art, and a source for writers, scholars and historians, Transference, Tradition, Technology is co-produced with the Art Gallery of Hamilton, Hamilton; and Indigenous Media Arts Group, Vancouver.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Coded Territories: Tracing Indigenous Pathways in New Media Art - Loft, Steve; Swanson, Kerry (University of Calgary Press, 2014)
This collection of essays provides a historical and contemporary context for Indigenous new media arts practice in Canada. The writers are established artists, scholars, and curators who cover thematic concepts and underlying approaches to new media from a distinctly Indigenous perspective. Through discourse and narrative analysis, the writers discuss a number of topics ranging from how Indigenous worldviews inform unique approaches to new media arts practice to their own work and specific contemporary works. Contributors include: Archer Pechawis, Jackson 2Bears, Jason Edward Lewis, Steven Foster, Candice Hopkins, and Cheryl L'Hirondelle.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé